Development and Evaluation of a Student-Led Mental Health Promotion Workshop to Address Community Needs for Marginalized Populations in Urban Northern Ontario, Canada - Vic Eton; Teresa Semalulu; Tiffany Desruisseaux; Zachary Kuehner; Esa Leinonen; Jessica McCann; Carmen Petrick; Jennifer T Hoy; Dyane Lagadouro; Athena Young; Jennifer McPhail (Journal of Student-Run Clinics, 2019)
Background: Compass North is a student-led health outreach initiative in Thunder Bay, Ontario, Canada. A current unmet need in Thunder Bay identified in a previously published community needs assessment is mental health services. Women, youth, senior, Indigenous, and LGBT2-SQ populations were disproportionately affected. In response to these perceived gaps in services, a subcommittee of Compass North developed, delivered, and evaluated mental health workshops.Methods: Affiliations with Shelter House Thunder Bay (SH) and Anishnawbe Mushkiki Thunder Bay Aboriginal Health Access Centre (AM) were established. Six interactive workshops were developed and delivered over eight months. Likert scale-based evaluation surveys gauging workshop participant and presenter satisfaction with content were used. Attendance and return attendance were additional markers of success.  Results: A total of 36 participant surveys were completed between both sites. Response rates were 74% and 84% at SH and AM, respectively. Workshop content was well-received by participants and helped address some unmet health education needs. Attendance increased with time at SH.Conclusions: These interactive workshops are one way of addressing unmet community needs in Thunder Bay while maintaining a community presence prior to establishing a fully functional student-run clinic (SRC). They comprise a potentially valuable stage in development of a SRC.